2012
DOI: 10.1128/jcm.01517-12
|View full text |Cite
|
Sign up to set email alerts
|

The Rise of Tropheryma whipplei: a 12-Year Retrospective Study of PCR Diagnoses in Our Reference Center

Abstract: Tropheryma whipplei is the causative agent of classic Whipple's disease (WD) and other clinical entities, such as localized infection. Asymptomatic carriers have also been reported, mainly based on the testing of fecal samples. Our objective was to undertake a retrospective analysis of molecular biology usage for the diagnosis of WD over a 12-year period in our reference center. We tested 27,923 samples from 15,473 patients. The number of patients tested and the number of patients with a positive PCR result fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 18 publications
4
31
1
2
Order By: Relevance
“…With the introduction of PCR, it became clear that the bacterium could also be found in other samples (18,40). Microscopy of biopsy samples is a costly and invasive method and therefore not frequently used for screening purposes and usually performed only to confirm the diagnosis in the case of a serious suspicion of infection.…”
Section: Carriage Of Tropheryma Whippleimentioning
confidence: 99%
See 2 more Smart Citations
“…With the introduction of PCR, it became clear that the bacterium could also be found in other samples (18,40). Microscopy of biopsy samples is a costly and invasive method and therefore not frequently used for screening purposes and usually performed only to confirm the diagnosis in the case of a serious suspicion of infection.…”
Section: Carriage Of Tropheryma Whippleimentioning
confidence: 99%
“…Although most Whipple's disease patients do not present any obvious neurological symptoms, postmortem investigation showed that 90% of brain and spinal cord specimens from both patients and presumed carriers revealed lesions of the CNS, meaning that CNS involvement is more common than expected from the clinical manifestations (33). Another indication for frequent neurological involvement is the presence of T. whipplei DNA in the cerebrospinal fluid (CSF) of patients with classic Whipple's disease even in the absence of evident neurological manifestations (40,130). The prognosis for patients with symptomatic central nervous system involvement remains poor, as major sequelae are seen in 25% of patients and 4-year survival rates are Ͻ75% (131).…”
Section: Classic Whipple's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Others, however, have reported a higher prevalence (7.24%) (17). These samples were sent from different countries to be analyzed in a tertiary center for WD, probably because of a suspicion of WD in symptomatic individuals, which may have contributed to this difference.…”
mentioning
confidence: 99%
“…The emergence of real-time PCR technology has substantially improved and facilitated the molecular detection of Tropheryma whipplei, the causative agent of Whipple's disease (2,3). In search of a specific and sensitive PCR protocol, several target genes have already been evaluated, including the 16S rRNA gene (4), the 16S-23S rRNA intergenic spacer region (5), the hsp65 gene (6), and certain repeated sequences (7).…”
mentioning
confidence: 99%